Monitoramento de temperatura em turbina de motordiesel de locomotiva com sensor a fibra ótica - Mezzadri, Felipe (2012)
This paper describes the fabrication, implementation and results of a fiber optic sensor based on Bragg gratings regenerated for measurement of high temperatures of the exhaust gases in a turbine diesel engine locomotive. The proposed sensor with an encapsulation with stainless steel parts which is laid down on the surface of the turbine. The sensor has been challenged undergoing field tests at varying engine power. In the laboratory the optical sensor was compared with a conventional thermocouple sensor. It was possible to demonstrate that the temperature values measured by the sensors, both the optical fiber sensor as the conventional follow the same trend of the power generated by the engine and thus demonstrated the efficiency of the operation of sensors measuring temperatures showing in turbine.